Design and Implementation of Hybrid Power Plant to Feed a Residential Area - Eyhab Abolaed Barkah; Ali A Alkharboushi; Abdulhamid Salim Alharam; Amjad Abdulsalam Alshafh; Mehdi Mohamed Baker (Surman Journal of Science and Technology, 2024)
This project was mainly focusing on possibility of building a solar wind hybrid power plant is to power the residential buildings in Zawia City which is ((Deela residential area)). The weather profile data for Solar and wind were studied and analyzed for the proposed area. Based on the power consumption; it has been decided that a 2.1 MW power plant is adequate choice to satisfy the demand. This load will be divided to 1.8 MW for the solar field and 0.3 MW for the wind farm according to the energy potential in the selected site. The system components and requirements were designed and specified using amount of software. The hybrid system costs including the initial costs, operation and maintenance costs have been calculated for a 20 years lifetime in order to calculate the electricity price and the payback period which is turned out to be (8.3 years).